Magnitudes of Anemia and Its Determinant Factors Among Lactating Mothers in East African Countries: Using the Generalized Mixed-Effect Model - Tusa, Biruk Shalmeno; Weldesenbet, Adisu Birhanu; Bahiru, Nebiyu; Enyew, Daniel Berhanie (Frontiers in Nutrition, 2021)
Background; The magnitude of anemia and its determinant factors among lactating mothers is far behind investigated regardless of its multivariate consequences. Even though few works are conducted on the magnitude of anemia and the determinants, most of them focused at country level and in different parts of countries. Therefore, the current study was aimed to determine the magnitude of anemia among lactating mothers and the determinant factors in Eastern Africa. Methods: From 9 East African countries, a total weighted sample of 25,425 lactating mother were included in the study. Determinate factors of anemia were identified using Generalized Linear Mixed Models (GLMM). Variables with p-value < 0.05 in the final GLMM model were stated to confirm significant association with anemia. Result: The magnitude of Anemia in east Africa was found 36.5% (95% CI: 35.55%, 36.75%) and in generalized liner mixed effect model, age, educational status, working status, living country, wealth index, ante natal care service, place of delivery, history of using family planning in a health facility, currently pregnant and visited by fieldworker in last 12 months were factors that have a significant association with anemia in lactating mothers Conclusion: In East Africa, more than one third of lactating mother have anemia. The odd of anemia was significantly decreased among young aged (15-34), primarily educated, currently working, Rwanda dweller and higher wealth index (middle and high). In addition, the likelihood of anemia was also decreased among lactating mothers who have Antenatal care, use family planning delivered in health facility, currently pregnant and visited by fieldworker. Therefore, promoting maternal care services (like family planning, ANC and health facility delivery) and field work visit by health extension worker is strongly recommended.